Translational strategies and challenges in regenerative medicine - Dimmeler, Stefanie; Ding, Sheng; Rando, Thomas A; Trounson, Alan (Nature medicine, 2014)
Our understanding of stem cell biology is increasing, but the translation of this knowledge into regenerative medicine therapies for aged or diseased tissues is proving challenging. In this Perspective, four experts in the field discuss strategies for overcoming the major hurdles facing the translational regenerative field. The scientific community is currently witnessing substantial strides in understanding stem cell biology in humans; however, major disappointments in translating this knowledge into medical therapies are flooding the field as well. Despite these setbacks, investigators are determined to better understand the caveats of regeneration, so that major pathways of repair and regrowth can be exploited in treating aged and diseased tissues. Last year, in an effort to contribute to this burgeoning field, Nature Medicine , in collaboration with the Volkswagen Foundation, organized a meeting with a panel of experts in regenerative medicine to identify the most pressing challenges, as well as the crucial strategies and stem cell concepts that can best help advance the translational regenerative field. Here some experts who participated in the meeting provide an outlook at some of those key issues and concepts.